Improving student learning outcomes through the use of Jigsaw learning - Thenu, Desty Marenska; Wambrauw, Hengky Lukas; Budirianto, Heru Joko; Damopolii, Insar (Univeritas Papua, 2023)
The research aims to apply jigsaw cooperative learning to improve student learning outcomes in the eighth grade of SMPN 10 Anggori Manokwari. This research is classroom action research. The research subjects were 36 students. Data were collected using learning achievement tests and observation sheets. The results showed that the students who were deaf in cycle I was 47.22% and experienced an increase in cycle II of 91.67%. This study concludes that applying the jigsaw cooperative learning model can improve student learning outcomes.